2021
DOI: 10.1093/chromsci/bmab124
|View full text |Cite
|
Sign up to set email alerts
|

Determination of B Vitamins by Double-Vortex-Ultrasonic Assisted Dispersive Liquid–Liquid Microextraction and Evaluation of their Possible Roles in Susceptibility to COVID−19 Infection: Hybrid Box–Behnken Design and Genetic Algorithm

Abstract: Objectives In this study, double-vortex-ultrasonic assisted dispersive liquid–liquid microextraction (DVUDLLME) was applied to determine the concentration of vitamin B9, 5-methyl tetrahydrofolate (5-MeTHF) and vitamin B12 in human serum samples. Methods High-performance liquid chromatography (HPLC) coupled with DVUDLLME was applied to analyze vitamins B in patients with Coronavirus disease (COVID-19). Then, significant variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
0
0
2
Order By: Relevance
“…Deschasaux-Tanguy et al reported that dietary intakes of folate were associated with a decreased probability of SARS-CoV-2 infection [60]. On the other hand, Akbari et al found no significant difference in the folate serum levels between the control group and COVID-19 patients [61]. Nevertheless, our findings are in line with a recent study by Pandya et al, which suggests a protective role of folates against SARS-CoV-2 infection thanks to their high affinity bond with viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Deschasaux-Tanguy et al reported that dietary intakes of folate were associated with a decreased probability of SARS-CoV-2 infection [60]. On the other hand, Akbari et al found no significant difference in the folate serum levels between the control group and COVID-19 patients [61]. Nevertheless, our findings are in line with a recent study by Pandya et al, which suggests a protective role of folates against SARS-CoV-2 infection thanks to their high affinity bond with viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Дефицит витамина B12 часто встречается у пожилых людей и больных СД2, эти же пациенты входят в группу риска тяжелого течения COVID-19. Кроме того, симптомы дефицита В12 сходны с осложнениями новой коронавирусной инфекции: чрезмерные воспалительные и окислительные реакции на стресс [16], поражения центральной нервной и сердечно-сосудистой систем и желудочно-кишечного тракта, несостоятельность иммунного ответа. Следовательно, восполнение этого дефицита могло бы снизить риск смерти и вероятность развития цитокинового шторма и дыхательной недостаточности [17,18].…”
Section: Reviewsunclassified
“…Даже в контрольной группе (без изначального дефицита В12) отмечен существенный прирост концентраций маркеров иммунитета, что свидетельствует о противовирусных иммунологических свойствах B12. Более позднее проспективное турецкое исследование больных с В12-пернициозной анемией также подтвердило восстановление количества лимфоцитов, активности NK-клеток и соотношения CD4+ : CD8+ после внутримышечного введения цианокобаламина [16]. Кроме того, в данном исследовании продемонстрировано повышение уровней дополнительных противовирусных компонентов иммунной системы, а именно комплемента С3 и С4 и иммуноглобулинов.…”
Section: дефицит B12 и иммунная системаunclassified